Earlier Prehistoric Activity and a Later Iron Age and Roman Field System at Beacon Lagoons, Kilnsea, East Riding of Yorkshire. Issue 1 (August 2014) - R, J; W, P; Alldritt, Diane; Carrott, John; Didsbury, Peter; Foster, Alison; Holst, Malin; Makey, Peter; Manby, Terry; Walker, Angela
Abstract : An archaeological strip, map and record exercise on behalf of the Environment Agency was undertaken as part of the Easington Wetlands Project. The excavations revealed earlier prehistoric activity, probably representing seasonal occupation at times of the year when intermittently available resources were abundant. This activity is dated by predominantly later Neolithic and early Bronze Age flints, two Bronze Age radiocarbon dates and later Bronze Age pottery. A Romano-British field system that may have had Iron Age origins was also identified. The pottery assemblage suggests the field system was in use up to the fourth centuryad .